2019
DOI: 10.3390/cells9010011
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the IL-18 Receptor Signaling Pathway Ameliorates Disease in a Murine Model of Rheumatoid Arthritis

Abstract: Interleukin (IL)-18 expression in synovial tissue correlates with the severity of joint inflammation and the levels of pro-inflammatory cytokines. However, the role of the IL-18/IL-18 receptor-alpha (Rα) signaling pathway in autoimmune arthritis is unknown. Wild-type (WT) and IL-18Rα knockout (KO) mice were immunized with bovine type II collagen before the onset of arthritis induced by lipopolysaccharide injection. Disease activity was evaluated by semiquantitative scoring and histologic assessment. Serum infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 53 publications
1
17
0
1
Order By: Relevance
“…In addition, many previous studies have been shown that serum and synovial IL‐18 levels are correlated with disease activity in RA and their pivotal role in maintaining the joint inflammation in RA, summarized in review papers 29 , 30 . The newest support for IL-18 therapeutic targeting in RA came from experiments with IL-18Rα knockout (KO) mice model of induced experimental arthritis 31 . The results from this study demonstrated that inhibition of the IL-18/IL-18Rα signaling pathway inhibited not only the proliferation of autoreactive T cells but also the suppression of IL-6, IL-18, TNF, and IFN-γ serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many previous studies have been shown that serum and synovial IL‐18 levels are correlated with disease activity in RA and their pivotal role in maintaining the joint inflammation in RA, summarized in review papers 29 , 30 . The newest support for IL-18 therapeutic targeting in RA came from experiments with IL-18Rα knockout (KO) mice model of induced experimental arthritis 31 . The results from this study demonstrated that inhibition of the IL-18/IL-18Rα signaling pathway inhibited not only the proliferation of autoreactive T cells but also the suppression of IL-6, IL-18, TNF, and IFN-γ serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…Since IL-18 intracellular signal transduction is also mediated by several kinases, crosstalk cannot be suppressed and it is difficult to block signal transduction with JAK inhibitors. Recently, a study using a murine CIA model has suggested that inhibition of cytokine signaling by the SOCS family constitutes a major negative feedback mechanism to prevent runaway inflammation [180]. The transcription of SOCS proteins is rapidly upregulated in cells stimulated with cytokines.…”
Section: Il-18 and The Pathogenesis Of Ramentioning
confidence: 99%
“…Additionally, IL-18 induces the production of IL-17 [ 82 ], IL-32 [ 75 ], IL-2, IL-2Rα, TNF-α, GM-CSF, prostaglandin E2, MMP3, chemokines [ 78 ], adhesion molecules, and angiogenic factors [ 82 ]. In murine models of RA, mice with knockdown of IL-18Rα (IL-18 receptor α) presented decreased levels of IL-6, IL-18, TNF-α, IFN-γ, and MMP3, as well as less severe disease progression [ 83 ], which can implicate the importance of this cytokine in the course of this affliction. A research study published by Yin et al revealed that curcumin suppressed the secretion of IL-18 in mouse bone marrow-derived macrophages [ 84 ].…”
Section: Ra Markers and Most Common Cytokines—potential Therapeutic Targetsmentioning
confidence: 99%